Comparing the safety and efficacy of remimazolam-based total intravenous anesthesia versus volatile agent-based anesthesia: a meta-analysis of randomized controlled trials - Ji-In Park; Hyo-Seok Na; Keum-O Lee; Jung-Hee Ryu; Hyun-Jung Shin (Korean Journal of Anesthesiology)
Background Remimazolam is a novel short-acting benzodiazepine that has recently been used for general anesthesia. This study compared the safety and efficacy of remimazolam-based total intravenous anesthesia (TIVA) and volatile agent-based anesthesia in adults undergoing general anesthesia. Methods We searched electronic databases including PubMed, Embase, CENTRAL, and Scopus for relevant studies. The primary outcome was the proportion of patients who experienced hypotension during surgery. Secondary outcomes included incidence of bradycardia, extubation time, duration in the post-anesthesia care unit hospital stay, and incidence of postoperative nausea and/or vomiting (PONV). We estimated the relative risk (RR) and mean difference with 95% CIs using a random-effects model. Results A total of 969 patients from 12 randomized controlled trials were included. The incidence of hypotension was 14% and 34% in the remimazolam and volatile agent groups, respectively. Remimazolam significantly lowered the incidence of hypotension (RR: 0.43, 95% CI [0.29–0.63], P = 0.0000, I2 = 26%). The remimazolam group had a PONV incidence of 13%, compared to 28% in the volatile agent group, indicating a significant difference (RR: 0.51, 95% CI [0.37–0.72], P = 0.0001, I2 = 15%). No significant differences were observed in the other outcomes. Conclusions Remimazolam-based TIVA demonstrated favorable hemodynamic effects, with a lower incidence of hypotension and similar bradycardia rates, compared to volatile agent-based anesthesia. Furthermore, the reduction in PONV supports the use of remimazolam-based TIVA as a valuable method for general anesthesia.